AML-associated mutation of nucleophosmin compromises its interaction with nucleolin - Šašinková, Markéta; Holoubek, Aleš; Otevřelová, Petra; Kuželová, Kateřina; Brodská, Barbora (The international journal of biochemistry & cell biology, 2018)
C-terminal mutations of the nucleolar protein nucleophosmin (NPM) are the most frequent genetic aberration detected in acute myeloid leukemia (AML) with normal karyotype. The mutations cause aberrant cytoplasmic localization of NPM and lead to loss of functions associated with NPM nucleolar localization, e.g. in ribosome biogenesis or DNA-damage repair. NPM has many interaction partners and some of them were proved to interact also with the mutated form (NPMmut) and due to this interaction thereby to be withdrawn from their site of action. We analyzed the impact of the mutation on NPM interaction with nucleolin (NCL) which is also prevalently localized into the nucleolus and cooperates with wild-type NPM (NPMwt) in many cellular processes. We revealed that the NCL-NPM complex formation is completely abolished by the mutation and that the presence/absence of the interaction is not affected by drugs causing genotoxic stress or differentiation. Deregulation resulting from changes of NCL/NPMwt ratio may contribute to leukemogenesis.
Keywords: nukleofosmin; Nucleolin; Oligomerization; Neoplasm Proteins; Cell Line, Tumor; HEK293 Cells; Humans; AML; Phosphoproteins; akutní myeloidní leukemie; Interaction; nukleolin; jaderné proteiny; fosfoproteiny; multiproteinové komplexy; Cell Nucleolus; mutace; buněčné jadérko; Nucleophosmin; Mutation; proteiny vázající RNA; nádorové proteiny; Nuclear Proteins; Multiprotein Complexes; Leukemia, Myeloid, Acute; nádorové buněčné linie; lidé; RNA-Binding Proteins; HEK293 buňky